Quais características influenciam a performance futura dos fundos de investimento de ações no Brasil ? - Lucena, Igor Macedo de (2014)
According to Jensen (1968), the mutual funds industry expansion is theoretically predicted by the Separation Theorem stated by Sharpe (1964), however with limitations in order to exceed the market in terms of risk-return performance measured by Jensen's alpha. In this broad discussion, this dissertation suggest an empirical exercise applied to a cross-section containing 243 stock funds, within the Ibovespa Active category, which aims to identify which financial, accounting and administrative variables are capable to predict the next year's value and the significance of the Jensen's alpha. Daily returns were extracted for all funds in 2011 and 2012, and were calculated classic metrics such as return, risk and performance. There were also extracted 24 monthly accounting balances and administrative informations for the period in question. Methodologically, the explanatory variables consist of descriptive statistics obtained from daily financial data and monthly accounting data, while the performances to be modeled are estimated using the Capital Asset Pricing Model (CAPM). Using this technic it was possible divide the funds into three groups, consisting of Loosers, Draw and Winners, according to their performances in relation to the Ibovespa index. Thus, it was discovered that only 71 funds were able to perform better than the Ibovespa Index during the year 2012. The estimation results of the ordered probit framework suggests that funds with higher performances measured by the Jensen's Alpha and with higher Sortino and Calmar ratios, associated with lower management fees tend to surpass the market in the next year. However, classical metrics like standard deviation, performance fees and Sharpe ratio (1964) were not significant. The model also suggests that the drawdown variable should be used as an efficient risk metric.